Characteristics of Strategic Human Resource Development Support System - Choiri (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
One of the fundamental changes in public management reform is the push to build a business-oriented entrepreneurial culture and the need to develop new human resources who have the ability to manage and implement reforms. It is clear that the current human resource development (HRD) approach is inadequate to ensure that civil servants acquire new skills. It is also not sufficient to create an enabling environment for government agencies to enhance organizational capabilities to undertake large-scale learning processes related to procedural and cultural changes. It is clear that human resource development should be placed more carefully within government structures. Therefore, one of the main challenges is to determine the traits that will enable strategic HR development to emerge in government institutions